KONSOLIDASI GERAKAN MILENIAL INDONESIA DALAM UPAYA MEMENANGKAN PASANGAN PRABOWO – SANDIAGA UNO DALAM PEMILIHAN UMUM PRESIDEN 2019 DI KABUPATEN SIDOARJO - Lailatul Fitriah; Dwi Windyastuti Budi Hendrarti (Jurnal Politik indonesia (Indonesian Journal of Politics), 2020)
This study aimed to determine the tendencies carried out by GMI Sidoarjo in the 2019 presidential election. GMI Sidoarjo is one of the community organizations that acts as a successful team winning the pair of candidates in the 2019 presidential election. This research is descriptive qualitative by using the theory of political participation from Samuel Huntington and Nelson. From the results of the study obtained several results, namely political participation carried out are collective, organized, legal and ineffective. Consolidation is done internally and externally. Then, the form of political participation in conducting elections is carried out with political discussion, outreach, campaigning and vote escort. The winning effort was unsuccessful, so the pair supported by the Indonesian Millennial Movement in Sidoarjo was defeated due to the lack of targeted support in fighting for votes in the 2019 presidential election.